A population‐based study of the effect of pregnancy history on risk of stillbirth. Issue 1 (28th October 2017) - Räisänen, Sari; Hogue, Carol J.R.; Laine, Katariina; Kramer, Michael R.; Gissler, Mika; Heinonen, Seppo
Abstract: Objective: To examine the effect of pregnancy history on the risk of stillbirth. Methods: In a population‐based cross‐sectional study, data were reviewed from all women aged at least 20 years with singleton pregnancies in Finland between 2000 and 2010. The primary outcome—stillbirth—was defined as fetal death after 22 gestational weeks or death of a fetus weighing at least 500 g. Results: Among 604 047 singleton pregnancies, the prevalence of stillbirth was 3.17 per 1000 deliveries. Prevalence was lowest for multiparous women without previous pregnancy loss after adjusting for major pregnancy complications associated with stillbirth (placenta previa, placental abruption, and pre‐eclampsia) and other confounders. Relative to these women, stillbirth prevalence was higher among multiparous women with previous spontaneous abortion and/or stillbirth (adjusted odds ratio [aOR] 1.20, 95% confidence interval [CI] 1.05–1.36), nulliparous women with no previous pregnancy loss (aOR 1.23, 95% CI 1.10–1.38), and nulliparous women with prior spontaneous abortion (aOR 1.43, 95% CI 1.18–1.74). Conclusion: Previous pregnancy loss was found to be an independent risk factor for stillbirth, irrespective of the number of prior deliveries. Abstract : Spontaneous abortion assessed as a part of pregnancy history was found to be an independent risk factor for stillbirth.